(untitled) (International Research in Economics and Finance, 2022)
This paper discusses The Political Economy of Customary Organizations in Rural Afghanistan by Jennifer Brick (2008) (hereafter, “the work”), which tries to ascertain whether public goods can be provided in a failed state and proposes a mechanism that provides social order as a public good. Brick achieves this by studying customary and non-customary organisations in rural Afghanistan and develops a theory to explain when a rural local authority might fulfil the purpose of public provision and governance. This paper demonstrates and analyses Brick’s findings, and proposes one main criticism to Brick’s quantitative research method.